2015
DOI: 10.1007/s00265-015-1975-0
|View full text |Cite
|
Sign up to set email alerts
|

Divergent oviposition preferences of sister species are not driven by nest survival: the evidence for neutrality

Abstract: Both adaptive and neutral trait evolution can contribute to divergence, but the relative contributions of the two remain unclear. Oviposition preference, a trait that has been demonstrated to contribute to divergence among populations, is often presumed to be an adaptive trait. Few studies explicitly test this assumption, however, and several researchers have demonstrated non-adaptive oviposition preferences in wildlife populations. In this study, we test whether adaptive divergence can explain current differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 66 publications
(68 reference statements)
1
8
0
Order By: Relevance
“…Specifically, successful nests were built higher in the vegetation, had more canopy cover, and were in higher elevation areas of the marsh than those that flooded. Several previous studies failed to find a consistent relationship between nest structures and nest success, despite strong evidence of nest site selection preferences for characteristics that confer resistance to flooding (Gjerdrum et al., ; Humphreys et al., ; Ruskin et al., ; Shriver et al., ). Our findings are consistent with these nest characteristics having a fitness effect, and the large sample size in our study (536 nests vs. 69 −160 nests in prior studies) may have allowed more power to detect small effect sizes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Specifically, successful nests were built higher in the vegetation, had more canopy cover, and were in higher elevation areas of the marsh than those that flooded. Several previous studies failed to find a consistent relationship between nest structures and nest success, despite strong evidence of nest site selection preferences for characteristics that confer resistance to flooding (Gjerdrum et al., ; Humphreys et al., ; Ruskin et al., ; Shriver et al., ). Our findings are consistent with these nest characteristics having a fitness effect, and the large sample size in our study (536 nests vs. 69 −160 nests in prior studies) may have allowed more power to detect small effect sizes.…”
Section: Discussionmentioning
confidence: 97%
“…Nest site selection is spatially random with respect to other nesting females (Bayard & Elphick, ; Gjerdrum et al., ), suggesting that structural characteristics of the nest itself may be more important to success than where the nest is located within the preferred nesting habitat (Gjerdrum et al., ). While prior research has found vegetation cover characteristics to be important in nest site selection, neither these vegetation characteristics, nor nest height (the height at which the nest is placed above the ground) and substrate elevation (the elevation of the marsh surface; see Figure ) have been found to consistently influence nest success (Gjerdrum et al., ; Humphreys, Elphick, Gjerdrum, & Rubega, ; Ruskin, Hodgman, Etterson, & Olsen, ; Shriver et al., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Etterson et al [ 24 ] compared two versions of the parameterized MCnest model to field-based predictions of the number of broods per female produced in Illinois populations of Eastern meadowlark ( Sturnella magna ) and dickcissel ( Spiza americana ). The Markov algorithm behind MCnest has also been adapted for use as a multistate competing risks estimation model and has been applied to the problem of estimation of stressor effects on wild bird populations [ 53 – 55 ], including two cases exploring the effects of environmental contaminants [ 56 , 57 ]. Etterson [ 4 ] also showed how the framework could be further adapted to estimate acute mortality of contaminants in field trials when carcass scavenging and imperfect detection make inference difficult.…”
Section: Discussionmentioning
confidence: 99%
“…When chicks died during nest flooding or predation events, we obtained tissue samples when possible. We determined nest failure or success based on evidence at the nest site (Ruskin et al, 2015). Briefly, we considered a nest successful if it was found empty when at least one nestling would have been 10 days old; we counted a nest successful if at least one chick fledged.…”
Section: Study Sites and Data Collectionmentioning
confidence: 99%